SCN8A and Its Related Epileptic Phenotypes - Praticò, Andrea; Gulizia, Carmela; Gangi, Gloria; Oliva, Claudia; Romano, Catia; Marino, Simona; Polizzi, Agata; Ruggieri, Martino; Falsaperla, Raffaele (Journal of Pediatric Neurology, 2021)
Sodium channelopathies are among the most common single-gene causes of epilepsy and have been considered model disorders for the study of genetic epilepsies. Epilepsies due to SCN8A pathogenic variants can present with a broad range of phenotypes varying from a severe epileptic encephalopathy with multiple types of drug-resistant seizure to neurodevelopmental delay, mental retardation, and electroencephalogram (EEG) findings of multifocal spike and waves (mostly in the temporal/parietal/occipital areas). In rare cases, benign familial infantile seizures and developmental delay with/without ataxia have been reported. A first-level, specific SCN8A Sanger's sequencing, although available, is rarely performed because the clinical phenotype is not strictly characteristic and several overlaps with other genetic epilepsies may occur. Given its indistinctive phenotype, diagnosis is usually performed through a specific gene panel for epileptic encephalopathies, early epilepsies, or genetic epilepsy in general, or through whole exome sequencing (WES) and more rarely through whole genome sequencing (WGS). Mutations in SCN8A occur as an autosomal dominant trait. The great majority of individuals diagnosed with SCN8A epilepsy do not have an affected parent, because usually SCN8A patients do not reproduce, and mutations are inherited as a “de novo” trait. In rare cases, SCN8A mutations may be inherited in the setting of parental germline mosaicism. SCN8A-related epilepsies have not shown a clear genotype–phenotype correlation, the same variants have been described with different clinical expressivity and this could be due to other genetic factors or to interacting environmental factors. There is no standardized treatment for SCN8A-related epilepsy because of the rarity of the disease and the unavailability of specific, targeted drugs. Treatment is based mainly on antiepileptic drugs which include classic wide-spectrum drugs such as valproic acid, levetiracetam, and lamotrigine. Sodium-channel blockers (phenytoin, carbamazepine, oxcarbazepine, and lamotrigine) have shown appreciable results in terms of seizure reduction, in particular, in patients presenting gain-of-function mutations. Nowadays, new potentially transformative gene therapy treatment approaches are currently being explored, allowing in the next future, a precision-based treatment directed against the gene defect and protein alterations.
Keywords: SCN8A; sodium channel; benign familial infantile seizures; epileptic encephalopathy; movement disorders